2017
DOI: 10.1515/enr-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone regulates granzyme K expression in rat testes

Abstract: Objective. Testosterone depletion induces increased germ cell apoptosis in testes. However, limited studies exist on genes that regulate the germ cell apoptosis. Granzymes (GZM) are serine proteases that induce apoptosis in various tissues. Multiple granzymes, including GZMA, GZMB and GZMN, are present in testes. Th us, we investigated which granzyme may be testosterone responsive and possibly may have a role in germ cell apoptosis aft er testosterone depletion.Methods. Ethylene dimethane sulfonate (EDS), a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In addition, cortisol is known as one of the primary hormones that define stress conditions, as it has been reported that it increases during stress conditions [9][10][11] and will be affected by the decreased testosterone level. Testosterone is an active hormone that regulates libido and supports spermatid elongation during spermiogenesis [12,13]. As a result, stress has a negative impact on growth rate, feed consumption, body weight, libido, and animal production [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cortisol is known as one of the primary hormones that define stress conditions, as it has been reported that it increases during stress conditions [9][10][11] and will be affected by the decreased testosterone level. Testosterone is an active hormone that regulates libido and supports spermatid elongation during spermiogenesis [12,13]. As a result, stress has a negative impact on growth rate, feed consumption, body weight, libido, and animal production [14].…”
Section: Introductionmentioning
confidence: 99%
“…E2 downregulated genes included the immune regulators GZMA and LECT2 [ 42 , 43 , 44 , 45 ]. The most upregulated gene by soy was SMAD6, which is an inhibitor of BMPs and TGF-b signaling, and in vitro experiments showed that SMAD6 overexpression blocks BMPs-induced osteoblast and chondrocyte differentiation [ 46 ].…”
Section: Resultsmentioning
confidence: 99%